RUQYAH: LISTENING TO QURANIC VERSES, A DISEASE TREATMENT STRATEGY - Kulsoom, Bibi (International Journal of Islamic and Complementary Medicine, 2024)
The global Muslim population has surpassed two million, and Islamic principles emphasize accepting teachings from the Holy Quran and Sunnah for theoretical and practical guidance. Among these teachings is the recommendation to seek healing through reciting the Quran, known as 'Ruqyah Shar'iyya.' Despite its significance, medical professionals in Muslim-majority countries often need more awareness of Ruqyah, leading to an overreliance on pharmacological treatments with potential side effects. This study aims to increase awareness among healthcare providers about authentic and updated knowledge regarding Islamic teachings related to disease treatment through listening to the Quran and supplications. Through a descriptive literature review, the research explores critical terms such as Ruqyah, shifa (healing), treatment by Quran, spiritual treatment, Islamic treatment, and supplication in various sources, including the Quran, Hadith books, Google Scholar, and PubMed. While pharmacological treatments remain the primary approach for many diseases, this study suggests that non-pharmacological strategies, such as Quran recitation (Ruqyah) and specific supplications, align with the recommendations of Prophet Mohammad (ﷺ). Training doctors, nurses, and healthcare providers in the Muslim community to incorporate Ruqyah into their practice or involving Ruqyah professionals for Muslim patients can offer additional treatment options. This approach promotes healing without side effects and enhances patients' patience, satisfaction, and overall well-being. Such practices improve quality of life and foster trust in the doctor-patient relationship.